Assessing Fracture Resistance of Restored Premolars with Novel Composite Materials: An In Vitro Study - Zahraa Abdulaali Al-Ibraheemi; Huda Abbas Abdullah; Nada Abdlameer Jawad; Julfikar Haider (Hindawi Limited, 2021)
During restorative treatment, premolars restored with resin filling materials using the conventional incremental-fill technique take longer restoration time and undermine the integrity of the tooth. The aim of this study was to assess fracture resistance of premolars restored by various types of novel bulk-fill composite resin materials. Forty-eight (n = 48) freshly extracted sound maxillary first premolars were used in this in vitro study. The teeth were divided into six groups, each having 8 specimens. Group A (positive control) was allocated for the intact teeth. For specimens in Groups B to F, a large cavity (Class-II MOD) was prepared with a standardized dimension of cavity (3 mm depth on the pulpal floor, 4 mm at the gingival seat, and 3 mm cavity width). Group B represented prepared teeth without any restoration. Group C, Group D, Group E, and Group F were restored with Tetric EvoCeram® incremental-fill (conventional), Beautifil bulk-fill, Filtek posterior bulk-fill, and SonicFill 2 bulk-fill restorative materials, respectively. All samples were finished and polished with an enhanced finishing kit and stored in distilled water for a month before the fracture resistance testing. All the samples were exposed to the axial loading (the speed of crosshead was 1 mm/min) in a computer-controlled universal testing machine (LARYEE, China) via a steel bar (6 mm in diameter) and the maximum applied force in Newton was recorded as the fracture resistance. One-way analysis of variance (SPSS 21) was used to compare the fracture resistance within the groups, and Tukey's post hoc test was used to determine the difference between the groups. The lowest value of fracture resistance was recorded for Group B, and the highest value was recorded for Group A followed by the values of Group D, Group C, Group F, and Group E. One-way ANOVA revealed a statistically significant difference between the groups (P<0.05). Nonsignificant difference was found between the premolars restored by bulk-fill and conventional composites. Among the bulk-fill restored specimens, Beautifil restorative demonstrated significantly higher fracture resistance in comparison with the other two bulk-fill restored specimen groups (SonicFill 2 and Filtek). Bulk-fill composite such as Beautifil could be an alternative option to conventional incremental-fill composite for premolar restoration.